2005
DOI: 10.1210/jc.2004-1852
|View full text |Cite
|
Sign up to set email alerts
|

Norethisterone Enanthate Plus Testosterone Undecanoate for Male Contraception: Effects of Various Injection Intervals on Spermatogenesis, Reproductive Hormones, Testis, and Prostate

Abstract: The goal of this study was to find the most favorable injection interval of norethisterone enanthate (NETE) plus testosterone undecanoate (TU) in terms of gonadotropin, sperm suppression, and prostatic effects. Fifty normal men were randomly assigned to receive NETE 200 mg plus TU 1000 mg every 8 wk (n = 10), every 12 wk (n = 10), every 6 wk for 12 wk and then every 12 wk (n = 10), and every 6 wk for 12 wk and thereafter TU 1000 mg plus placebo every 12 wk (n = 10), and placebo plus placebo every 6 wk for 12 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(56 citation statements)
references
References 21 publications
1
53
0
2
Order By: Relevance
“…Concluding our findings, the marmoset is a NHP model that would facilitate the measurement of fertility as an endpoint in a contraceptive trial but is obviously resistant to TU and NETE, which were shown to be effective suppressors of spermatogenesis in humans (Kamischke et al 2002, Kamischke & Nieschlag 2004, Meriggiola et al 2005. Although testicular volumes dropped and the endocrine axis responded as expected, fertility was, if at all, only mildly influenced by the administration of androgens and progestins and a reliable contraceptive effect of TU and NETE treatment is lacking in this animal model.…”
Section: Nete and Tu Contraception Fails In Marmosetsmentioning
confidence: 54%
See 1 more Smart Citation
“…Concluding our findings, the marmoset is a NHP model that would facilitate the measurement of fertility as an endpoint in a contraceptive trial but is obviously resistant to TU and NETE, which were shown to be effective suppressors of spermatogenesis in humans (Kamischke et al 2002, Kamischke & Nieschlag 2004, Meriggiola et al 2005. Although testicular volumes dropped and the endocrine axis responded as expected, fertility was, if at all, only mildly influenced by the administration of androgens and progestins and a reliable contraceptive effect of TU and NETE treatment is lacking in this animal model.…”
Section: Nete and Tu Contraception Fails In Marmosetsmentioning
confidence: 54%
“…Concerning testosterone, the permanent presence of enhanced levels could result in a certain resistance in the target organs (Takahashi et al 1985, Li et al 2005 and an accelerated clearance of exogenous androgens was reported (Mohle et al 2002, reviewed in Li et al (2005). Owing to this specific endocrine condition, we adapted the dosing of TU in our experiments and administered w3.5-fold higher dose compared with the amount recommended for human use (Kamischke et al 2001, Meriggiola et al 2005. However, before our experiments were performed, no experience existed about effects of TU/NETE on spermatogenesis in NHP species.…”
Section: Introductionmentioning
confidence: 99%
“…Four MENT implants induced azoospermia or severe oligozoospermia (sperm count !1!10 6 /ml) in 82% and 100% of subjects during the first and second 6-month periods of treatment respectively. Thus, during the last 6 months of treatment, MENT alone was as effective as testosterone undecanoate plus NET enanthate administered at 8-week intervals (Meriggiola et al 2005).…”
Section: Discussionmentioning
confidence: 93%
“…A number of studies have shown that combination of androgens and androgenic progestins such as levonorgestrel (LNG), etonogestrel (ENG), and norethisterone (NET), which are all 19-nortestosterone derivatives, increases the rate of azoospermia. This combined method allows reduction of the high dose of testosterone needed to suppress gonadotropins and its secondary adverse effects, while maintaining the beneficial peripheral actions of testosterone and, therefore, its potential utility as a male contraceptive (Meriggiola & Bremner 1997, Anderson & Baird 2002, Meriggiola et al 2005, Walton et al 2007). Although it is well known that some progestins can effectively suppress gonadotropin secretion and have a direct inhibitory effect on Leydig cell steroidogenesis, it remains to be seen whether the hormonal combination has an additive agonist-antagonist androgenic effect.…”
Section: Introductionmentioning
confidence: 99%
“…norethisterone and TU. 83,84 8-week intervals of treatment had a higher azoospermic rate than 12-week treatment. No short-term changes in the prostate were seen.…”
Section: Norethisterone Nestorone Gelmentioning
confidence: 83%